Argumentativeness of Bewildering and Reception Effectiveness in Models of Poetic Heritage - Bilal , Doha (Dirasat: Human and Social Sciences, 2023)
This research laid out an objective represented in pinpointing the lurking places of bewilderment and ways of persuasion in models of the poetic heritage of poets who held the flag of bewilderment and creativity, so they immortalized their poems, which implied deep vision and inclusiveness of the ego, the universe, and things. The research also concerned itself with the recipient, and the impact poetry has in dazzling him, and then his submission both emotionally and rationally to the poetic say purport. The research concluded that bewilderment has its causes relevant to text- characterizing elements, embodied in shifting, breaking expectation horizon, and functionalization of various forms of allegory. These reasons do make the poetic text excellently wonderful and argumentative; as they make the recipient partner and effective intellectual discussant, when he preoccupies his thought in reflection and thinking, and this dazzling advanced the recipient up because it is not a transient spiritual agitation; as it allures the recipient through a wonderful argumentative context.